Synchronous Periprosthetic Joint Infections: A Scoping Review of the Literature - Andrea Sambri; Emilia Caldari; Michele Fiore; Claudio Giannini; Matteo Filippini; Lorenzo Morante; Claudia Rondinella; Eleonora Zamparini; Sara Tedeschi; Pierluigi Viale; Massimiliano De Paolis (Diagnostics, 2022)
Prosthetic joint infections (PJIs) occurring in multiple joints at the same time (synchronous PJI) are an extremely rare complication, frequently associated with bacteremia, and are associated with high mortality rates. The presence of three or more prosthetic joints, rheumatoid arthritis, neoplasia, bacteremia and immune-modulating therapy seem to be the recurring risk factors for synchronous PJI. In case of PJIs, all other replaced joints should be considered as potentially infected and investigated if PJI is suspected. Treatments of synchronous multiple PJIs vary and must be decided on a case-by-case basis. However, the advantages of one-stage exchange seem to outweigh the two-stage protocol, as it decreases the number of necessary surgical procedures. Nonetheless, too few studies have been conducted to allow firm conclusions about the best handling of synchronous PJI. Thus, additional studies are needed to understand this devastating complication and to design the most appropriate diagnostic and therapeutic path.